Proceso de Atención de Enfermería en paciente de 32 años con 23 semanas de gestación y placenta previa marginal. - Chora Guamán, Leyddy Cristina (2020)
Placenta previa is defined as the complication that occurs when the placenta covers the opening cervix and this can be total or partial (Gallegos, 2018). The placenta previa currently affects 1 in 200 pregnant women, this pathology is considere done of the main causes of bleeding during pregnancy, since it prevents mothers from giving brith through natural childbirth, the risk factrs that triggers a placenta previa isa ge over 35 years, history of previious surgeries, such as a cessarean section or the removal of uterine fibroids (Pernales,2015). The purpose of this case study is to apply and develop the Nursing Care Process (PAE) in a 32-year-old patient in a 23-week gestation state with a diagnosis of marginal placenta previa, using the NANDA, NIC and NOC taxonomies. The purpose of applying the nursing care process is to be able to provide comprehensive care to through interventions that will be provided during her hospital stay, until her complete well-being is achieved.